On female body experience : "Throwing like a girl" and other essays - Young, Iris Marion, 1949- (Studies in feminist philosophy., 2005)
Written over two decades, these essays describe diverse aspects of women's lived body experience in modern Western societies. Young combines theoretical description of experience with normative evaluation of the unjust constraints on their freedom & opportunity that continue to burden many women.